2022
DOI: 10.1002/ca.23895
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of an integrated anatomy mobile app

Abstract: Curricular hours for anatomical sub‐disciplines (gross anatomy, embryology, histology, and neuroanatomy) continue to decline, while medical schools are simultaneously transitioning to systems‐based, vertically integrated curricula. This requires students to learn and integrate all basic science content for a learning block prior to the summative assessment. Currently, no educational technology resource exists that integrates the four anatomical sub‐disciplines into a single resource to supplement integrated cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In 19 (63%) studies, the learning effectiveness of medical school students in anatomy education with mobile applications was investigated, and positive feedback was received from the students. In addition, students said that learning is more permanent and takes place in a shorter time (Bork et al, 2021;Chandrasekaran et al, 2021;Fernández-Alemán, Lopez-Gonzalez, et al, 2016;Gnanasegaram et al, 2020;Golenhofen et al, 2020;Harmon, Burgoon, & Kalmar, 2022;Jamali et al, 2015;Kurniawan & Witjaksono, 2018;Küçük et al, 2016;Lazarus et al, 2017;Mayfield, Ohara, & O'Sullivan, 2013;Mogali et al, 2019;Morris et al, 2016;Pickering, 2015;Raney, 2016;Stewart & Choudhury, 2015;Stirling & Birt, 2014;Traser et al, 2015;Wilkinson et al, 2020). However, in 6 (20%) studies, students stated that cadaveric education was easier, internet access outside the school was problematic, they had difficulty in downloading programs to their personal devices and they could not use the programs because they were paid.…”
Section: The Effect Of Anatomy Learning With a Mobile Application On ...mentioning
confidence: 99%
See 4 more Smart Citations
“…In 19 (63%) studies, the learning effectiveness of medical school students in anatomy education with mobile applications was investigated, and positive feedback was received from the students. In addition, students said that learning is more permanent and takes place in a shorter time (Bork et al, 2021;Chandrasekaran et al, 2021;Fernández-Alemán, Lopez-Gonzalez, et al, 2016;Gnanasegaram et al, 2020;Golenhofen et al, 2020;Harmon, Burgoon, & Kalmar, 2022;Jamali et al, 2015;Kurniawan & Witjaksono, 2018;Küçük et al, 2016;Lazarus et al, 2017;Mayfield, Ohara, & O'Sullivan, 2013;Mogali et al, 2019;Morris et al, 2016;Pickering, 2015;Raney, 2016;Stewart & Choudhury, 2015;Stirling & Birt, 2014;Traser et al, 2015;Wilkinson et al, 2020). However, in 6 (20%) studies, students stated that cadaveric education was easier, internet access outside the school was problematic, they had difficulty in downloading programs to their personal devices and they could not use the programs because they were paid.…”
Section: The Effect Of Anatomy Learning With a Mobile Application On ...mentioning
confidence: 99%
“…In the other 2 (6%) studies, it was observed that the anatomy final exam results of the experimental groups were higher, but there was a decrease in their cognitive levels (Bork et al, 2021;Küçük et al, 2016). 8 (26%) of the studies included in the research are exploratory and consist of articles that are not compared (Golenhofen et al, 2020;Harmon et al, 2022;Havens et al, 2020;Jamali et al, 2015;Kurniawan & Witjaksono, 2018;Pickering, 2015;Stewart & Choudhury, 2015). These articles have made no direct comparison between mobile learning and other learning experiences and methodologies.…”
Section: Surveymentioning
confidence: 99%
See 3 more Smart Citations